Modeling of plasmonic semiconductor THz antennas in square and hexagonal array arrangements - Gruessing, Soenke; Witzigmann, Bernd; Roemer, Friedhard; Capellini, Giovanni; Alvarado, Carlos; Klesse, Wolfgang M.; Hardt, Elena; Piehler, Jacob; You, Changjiang; Flesch, Julia (Proceedings of SPIE - The International Society for Optical Engineering, 2020)
Here, we present 3D solutions of Maxwell's equations using the finite element method (FEM) for sub-wavelength plasmonic THz antennas in array configurations. We show that mutual coupling between neighboring antennas causes the arrays spectral response to change with different array densities and arrangements. The simulation results of the spectral response of the antennas are in very good agreement to the experiments. Finally, in order to investigate the sensing performance of the antennas, simulations with different feed gap materials were carried out.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Antenna; Bio-sensing; Field enhancement; Germanium; Plasmonic; Proteins; THz